List Prodziekana Wydziału Teologii KUL dra hab. Ireneusza Lewdonia OFM, prof. KUL. - Ledwoń, Ireneusz (The Biblical Annals, 2016)
List Prodziekana Wydziału Teologii KUL dra hab. Ireneusza Lewdonia OFM, prof. KUL.